Severity of anxiety moderates the association between neural circuits and maternal behaviors in the postpartum period - Guo, Chaohui (Cogn Affect Behav Neurosci, 2018)
Neuroimaging research has suggested that activity in the amygdala, center of the socioemotional network, and functional connectivity between the amygdala and cortical regions are associated with caregiving behaviors in postpartum mothers. Anxiety is common in the early postpartum period, with severity ranging from healthy maternal preoccupation to clinical disorder. However, little is known about the influence of anxiety on the neural correlates of early caregiving. We examined these relationships in a community cohort of 75 postpartum women (ages 18–22; predominantly low-SES, minority race) who listened to infant cry sounds while undergoing an fMRI assessment. Maternal self-reported symptoms of anxiety were mostly within the subclinical range. Positive and negative caregiving behaviors during filmed face-to-face mother–infant interactions were coded by independent observers. The results from whole-brain analyses showed that anxiety severity moderated the brain–maternal behavior relationships. Specifically, our results showed that the higher a mother’s anxiety, the stronger the association between positive caregiving (i.e., maternal warmth and involvement) and amygdala–right posterior superior temporal sulcus (amygdala–RpSTS) functional connectivity. These results remained significant when we controlled for symptoms of depression and contextual variables. These findings suggest that functional connectivity between the amygdala and a social perception region (RpSTS) plays a particularly important role for anxious mothers in facilitating their positive parenting. These findings extend our understanding of the specific neural circuits that support positive maternal caregiving in the context of maternal anxiety, and they may help inform the future design of personalized and effective interventions.